Development of a Local Wisdom-Based Social Studies Module to Foster Character Education among Junior High School Students in East Lombok - Irwan, Mulyadi; Badarudin, Badarudin; Subhani , Armin (Sumber Belajar Sejahtera, 2026)
This study aims to develop, validate, and examine the effectiveness of a local wisdom-based Social Studies (IPS) teaching module in fostering character education among junior high school students. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants included eighth-grade students of SMP Negeri 1 Terara, East Lombok. The results indicate that the developed module is valid, practical, and effective. The expert validation results show high validity, with scores of 91.6% for content, 75% for media, and 77.77% for language, resulting in an overall average of 81.46% (very valid category). The practicality test reveals a user response score of 88.9%, categorized as very good, indicating that the module is easy to use and engaging in classroom learning. Furthermore, the effectiveness test demonstrates a significant improvement in students’ character education, as indicated by an N-Gain score of 0.54 (moderate category). The paired-sample t-test shows a statistically significant difference between pretest and posttest scores (p < 0.05), while the effect size (Cohen’s d = 0.76) indicates a moderate to high impact of the intervention. The novelty of this study lies in the systematic integration of Sasak local wisdom values into a structured Social Studies module using the ADDIE model, supported by empirical validation of its effectiveness. This study contributes to the development of culturally responsive instructional materials that enhance character education through contextually relevant learning.